Photooxidation of phytochemicals in food and control: a review. Issue 1 (15th June 2017) - Lu, Baiyi; Zhao, Yajing
Abstract : Phytochemicals are widely present in food and have been confirmed to be bioactive, thereby contributing to human health. However, some phytochemicals are sensitive to light owing to their structures and may suffer from photodegradation, especially when sensitizers exist, resulting in sensory quality change, nutrient loss in food, and even the formation of toxic compounds. The photooxidation of phytochemicals occurs through three different mechanisms: (1) by directly absorbing luminous energy, (2) with triplet‐excited state sensitizers through electron transfer or proton transfer (type I photooxidation), and (3) with singlet oxygen produced by O2 (type II photooxidation). On the basis of these mechanisms, adequate antioxidants can be added to quench the triple‐excited state sensitizers or singlet oxygen to protect against the photooxidation of phytochemicals in food. Here, we summarize and discuss the possible pathways and products of the photooxidation of phytochemicals that have been reported and the relationships between structures and photooxidation. We also propose some control measures, with special attention paid to the potential abilities of phytochemicals in the prevention of food photooxidation.